The Ratio of MicroRNA-21 to MicroRNA-195 as a Predictive and Prognostic Biomarker of Colorectal Carcinoma - Wijayana, Kamal Agung; Handaya, Adeodatus Yuda; Inayati, Nor Sri; Novrial, Dody (Asian Pacific Journal of Cancer Biology, 2025)
Introduction: Colorectal carcinoma (CRC) is the fourth leading cause of cancer-related death worldwide and the third most common cancer in Indonesia. Due to its asymptomatic nature, CRC is often diagnosed at an advanced stage, making early detection critical. MicroRNAs (miRNAs), small non-coding single-stranded RNA molecules, have emerged as potential biomarkers for cancer. Objective: This study aimed to determine the ratio profile of miR-21 and miR-195 as predictive and prognostic factors in colorectal carcinoma patients in Margono Soekarjo Hospital, Purwokerto, Indonesia. Methods: This study was conducted with a cross-sectional study design on 31 colorectal carcinoma patients during the 2018-2020 period who still had remaining paraffin-embedded tissue blocks at the Anatomical Pathology Laboratory of Margono Soekarjo Hospital, Purwokerto, Indonesia. The expression levels of miR-21 and miR-195 were analyzed using quantitative polymerase chain reaction (qPCR). The Pearson correlation test assessed the association between miRNA expression and clinicopathological parameters. Result: This study revealed that high miR-21 expression levels were significantly associated with poor prognosis in colorectal carcinoma patients, with p values of 0.027 and r = 0.398. Low miR-195 expression levels were significantly associated with poor colorectal carcinoma prognosis, with p values of 0.002 and r=0.533. A high miR-21/miR-195 expression levels ratio is significantly associated with the advanced colorectal carcinoma stage, with p values of 0.016 and r = 0.429. Conclusion: A High ratio of miR-21/ miR-195 correlates with the advanced stage of colorectal carcinoma. The expression ratio of miR-21 to miR-195 may be a potential predictive and prognostic biomarker in colorectal carcinoma.